2023
DOI: 10.1609/aaai.v37i11.26506
|View full text |Cite
|
Sign up to set email alerts
|

SumREN: Summarizing Reported Speech about Events in News

Abstract: A primary objective of news articles is to establish the factual record for an event, frequently achieved by conveying both the details of the specified event (i.e., the 5 Ws; Who, What, Where, When and Why regarding the event) and how people reacted to it (i.e., reported statements). However, existing work on news summarization almost exclusively focuses on the event details. In this work, we propose the novel task of summarizing the reactions of different speakers, as expressed by their reported statements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…The Multi-News dataset (Fabbri et al, 2019) is proposed for multi-document news summarization, in which the input is a set of news documents. The SumREN dataset (Reddy et al, 2023) is constructed for reported speech summarization that aims to summarize the reported statements made by a specific person in news documents. Other text summarization datasets focused on summarizing scientific articles (Cohan et al, 2018;Lu et al, 2020), legal documents (Kornilova and Eidelman, 2019), events (Ghalandari et al, 2020;Yoon et al, 2023;, or dialogues (Gliwa et al, 2019;Zhu et al, 2021;.…”
Section: Text Summarization Datasetsmentioning
confidence: 99%
“…The Multi-News dataset (Fabbri et al, 2019) is proposed for multi-document news summarization, in which the input is a set of news documents. The SumREN dataset (Reddy et al, 2023) is constructed for reported speech summarization that aims to summarize the reported statements made by a specific person in news documents. Other text summarization datasets focused on summarizing scientific articles (Cohan et al, 2018;Lu et al, 2020), legal documents (Kornilova and Eidelman, 2019), events (Ghalandari et al, 2020;Yoon et al, 2023;, or dialogues (Gliwa et al, 2019;Zhu et al, 2021;.…”
Section: Text Summarization Datasetsmentioning
confidence: 99%